(untitled) (International Journal of Environment, 2013)
The aim of the present study was to depict the preliminary data on occurrence of zooplanktons of Dakor Sacred Wetland (DSW) Central Gujarat, India. The samples of zooplanktons were collected from three permanent sampling stations for one year (June 2012 to May 2013) at 15 days interval. The zooplankton population was represented by a total of 36 genera and 39 species dispersed amongst Ciliophora (16 species), followed by Zooflagellata, Rhizopoda and Rotifera (6 species), Cladocera (3 species) while Copepoda and Ostracoda (1 species). Species such as Thecamooeba verrucosa Ehrenberg, Placus luciae Kahl, Spasmostoma viride Kahl, Cyclops sp., Daphnia lumholtzi G.O. Sars, were found abundant in all the study sites, while some chunk of species were classified as rare 43.5% (n=17) and the remaining were recorded as common. DOI: http://dx.doi.org/10.3126/ije.v1i1.8527 International Journal of Environment Vol.1(1) 2013: 46-55